A Comparative Study of Household Women in Delhi NCR on Consumer Perception Towards Milk and Milk Products - Pallathadka, Laxmi Kirana; Pallathadka, Harikumar; Devi, Takhelchangbam Brajeshwari (Integrated Journal for Research in Arts and Humanities, 2022)
Milk and its derivatives are a necessary component of a family's diet. It is precisely this kind of food that offers the critical nourishment required for people to be healthy. Milk is also a source of revenue for cattle ranchers. Consumer perception is essentially the consumer's behavioral habit while acquiring products or services (Jisana, 2014). Companies pay close attention to their consumers' requirements and requests to please them and benefit from increased sales. Every company's marketing department is focused on developing methods for expanding their customer base via effective advertising and promotion of their goods. However, customers prefer to patronize independent milk vendors, particularly those not branded, when selling milk and milk products. They decide to buy milk based on their reflection, regardless of whether they can obtain the highest quality goods. This research aims to decipher consumer behavior toward milk and related products, particularly in Delhi and from the perspective of women homemakers. A study of 103 households in the Delhi NCR was conducted to ascertain their preferences for milk and milk products based on the brand of the product. The research shows a considerable variation in consumers' preferences for branded and unbranded milk and milk products.